2019
DOI: 10.1007/s40520-019-01180-z
|View full text |Cite
|
Sign up to set email alerts
|

Older persons with signs of frailty in a home-based physical exercise intervention: baseline characteristics of an RCT

Abstract: Background Increasing the level of physical activity among persons with signs of frailty improves physical functioning. There is a lack of long-term supervised physical exercise intervention studies including a validated definition of frailty. Aims To present baseline characteristics of persons with signs of frailty participating in a randomized long-term home-based physical exercise trial (HIPFRA), and to study associations between the severity of frailty, functional independence and health-related quality-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Several studies have demonstrated the short‐term benefits of a multicomponent intervention on physical performance and frailty 10,14,17,18,33‐37 . Most studies included exercise and nutritional supplementation in the intervention; however, neither the duration of the intervention nor the follow‐up period exceeded 12 months 10,14,18,19,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the short‐term benefits of a multicomponent intervention on physical performance and frailty 10,14,17,18,33‐37 . Most studies included exercise and nutritional supplementation in the intervention; however, neither the duration of the intervention nor the follow‐up period exceeded 12 months 10,14,18,19,38 .…”
Section: Discussionmentioning
confidence: 99%
“…15 As a strength, our study was a rigorously performed RCT with good compliance. Furthermore, our sample was identified as frail or pre-frail at baseline 41 based on two validated frailty assessments. 6,16 We also used validated measurements to assess functioning and physical performance, and the proportion of missing measurements during the intervention year was very low (13% at 12 months).…”
Section: Discussionmentioning
confidence: 99%
“…8 Two of the phenotype criteria were slightly modified. 23 To define "low physical activity" we used 30 minutes per week as a cut-off value.…”
Section: Participantsmentioning
confidence: 99%
“…Mean total costs incurred by healthcare and social services per person-year during the first 12 months were 1.60-fold (95% CI 1. 23 We analyzed the effects of the intervention on HRQoL over 12 months, covering 96% (n=144) of the participants in the exercise group and 95% (n=141) of those in usual care. In the usualcare group the mean HRQoL score decreased significantly by 0.037 compared with the exercise group, which maintained the baseline level (p for group <0.001, time p=0.002, interaction p=0.002) (Figure 2).…”
Section: Secondary Outcomesmentioning
confidence: 99%